ANALYSIS OF EFFECT OF CAPR, DAR, ROA AND SIZE ON TAX AVOIDANCE - Akbar, Adil; Hakiman Thamrin (Dinasti International Journal of Management Science, 2020)
This study aimed to identify the effect of the independent variable capital intensity (CAPR), return on assets (ROA), debt to asset ratio (DAR), and the size of the company (SIZE) on tax avoidance (CETR) as dependent variable. This study tested using multiple linear regression analysis with the SPSS 25 program with a causality and comparative approach using cross sectional data. The results of the study in 2015 showed that the capital intensity and debt to asset ratio does not affect on tax avoidance, while return on assets and company size have significant negative effect on tax avoidance. In 2017, showed that the capital intensity, debt to asset ratio, and company size does not affect on tax avoidance, while return on assets has a significant negative effect on tax avoidance. Hypothesis testing results indicate that the independent variables simultaneously in 2015 and 2017 affect the dependent variable.